Awareness of an obstetric population about environmental tobacco smoking - Ghadeer K Al-Shaikh (Journal of Family and Community Medicine, 2014)
Background and Objectives: The reported rate of women′s smoking is typically low. However, many pregnant women are exposed to environmental tobacco smoke (ETS), which could affect their own health and the health of their growing fetus. The aim of this study was to estimate the magnitude of the problem of exposure to ETS and assess the awareness of postpartum women to ETS and its possible effects. Designs and Settings: This was a cross-sectional study conducted on 1182 postpartum women at a university hospital in Riyadh, Saudi Arabia, between 1 st January and 30 th June, 2012. Materials and Methods: A structured questionnaire was used for data collection. Factors associated with the level of understanding of the possible effects of ETS exposure were analyzed. Results: The majority of the participating women knew that exposure to ETS had adverse effects on maternal and fetal health (>80%), but their knowledge of the specific effects on fetal health was limited. The level of mothers′ education was found to be associated with better knowledge of effects on mother and fetal health (P < 0.01). Conclusion: This study revealed that pregnant women in our sample had limited knowledge of the specific effects of ETS on fetal health. This shortcoming in knowledge needs to be addressed by improving health.